ANALISIS DU PONT SYSTEM DALAM MENGUKUR KINERJA KEUANGAN PT. BUKIT ASAM TBK TAHUN 2020 – 2022 - Parasati, Yuanita Ayu; Sari, Pipit Novila; WA, Shinta Merinda (Journal of Accounting Taxing and Auditing (JATA), 2024)
AbstractRevenue is income generated in the implementation ordinary activities of the entity and are known by different names such as sales, imbalance, interest, dividends, royalties and rents. PT. Bukit Asam Tbk has grown over the last five years, from 2018 to 2022. This fact is used to analyze PT. Bukit Asam Tbk's financial performance from 2020 to 2022. This is a quantitative research employing time series data, with the population being all of PT. Bukit Asam Tbk's financial statements from 2020 to 2022. The balance sheet and profit and loss statements of PT. Bukit Asam Tbk 2020-2022 are covered in this research. As a data collection approach, this research relies on literature and documents. Net Profit Margin (NPM), Total Asset Turnover (TATO), and Return on Assets (ROA) are the analytical techniques applied. Based on data analysis results, PT. Bukit Asam Tbk's financial performance, as measured using the Du Pont System analysis is poor, with the value of the Net Profit Margin (NPM), Total Assets Turnover (TATO), and Return on Assets (ROA) ratios falling below the industry average Keywords : Net Profit Margin (NPM), Total Asset Turnover (TATO), and Return on Assets (ROA), Financial performance AbstrakPendapatan adalah pendapatan yang dihasilkan dalam pelaksanaan aktivitas biasa suatu entitas dan dikenal dengan berbagai nama seperti penjualan, ketidakseimbangan, bunga, dividen, royalti, dan sewa. PT. Bukit Asam Tbk telah berkembang selama lima tahun terakhir, yaitu dari tahun 2018 hingga tahun 2022. Fakta ini digunakan untuk menganalisis PT. Kinerja keuangan Bukit Asam Tbk tahun 2020 sampai dengan tahun 2022. Penelitian ini merupakan penelitian kuantitatif dengan menggunakan data time series, dengan populasi seluruh PT. Laporan keuangan Bukit Asam Tbk tahun 2020 sampai dengan tahun 2022. Neraca dan laporan laba rugi PT. Bukit Asam Tbk 2020-2022 tercakup dalam penelitian ini. Sebagai pendekatan pengumpulan data, penelitian ini mengandalkan literatur dan dokumen. Net Profit Margin (NPM), Total Asset Turnover (TATO), dan Return on Assets (ROA) merupakan teknik analisis yang digunakan. Berdasarkan hasil analisis data, PT. Kinerja keuangan Bukit Asam Tbk yang diukur dengan analisis Du Pont System kurang baik dengan nilai rasio Net Profit Margin (NPM), Total Assets Turnover (TATO), dan Return on Assets (ROA) yang berada di bawah rata-rata industry. Kata Kunci : Net Profit Margin (NPM), Total Asset Turnover (TATO), and Return on Assets (ROA), Kinerja Keuangan